2022
DOI: 10.1016/j.ejso.2021.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality treatment of undifferentiated pleomorphic soft tissue sarcoma of the extremity (eUPS) in the elderly

Abstract: Introduction: This subgroup analysis of undifferentiated pleomorphic soft tissue sarcoma of the extremity (eUPS) from the PERSARC collaborative group aimed to achieve a more personalized multimodality treatment approach for primary eUPS in elderly patients. Material and methods: A multicenter retrospective study including primary high-grade eUPS surgically treated with curative intent between 2000 and 2016. Overall survival (OS), local recurrence (LR) and distant metastasis (DM) curves were calculated by Kapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The results of our study were consistent with previous studies. 7-9 Bleckman et al 12 revealed that the OS of older patients decreased significantly more than those of younger patients. Vodanovich et al 9 reported that older age, lower extremity location, and positive surgical margins were risk factors for OS of patients with undifferentiated sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study were consistent with previous studies. 7-9 Bleckman et al 12 revealed that the OS of older patients decreased significantly more than those of younger patients. Vodanovich et al 9 reported that older age, lower extremity location, and positive surgical margins were risk factors for OS of patients with undifferentiated sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The management of limb spindle cell sarcomas requires a comprehensive approach that considers the tumor’s behavior[ 8 ], individual patient factors, and the potential risks and benefits of various treatment options. Surgery is typically the primary treatment option[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A group based in Leiden (the Netherlands) have used a subset of their cohort to describe a more focused approach in treating undifferentiated pleomorphic soft-tissue sarcoma of the extremity (eUPS) in the elderly population. 7 Overall, a large study cohort of 703 cases of eUPS in in older patients were identified and formed the basis of the study. From an outcomes perspective, the authors reported that the five-year overall survival was found to be 35.4%, with reported local recurrence occurring in 17.7% and distant metastases found in 24.6%.…”
Section: Multimodality Treatment Of Undifferentiated Pleomorphic Soft...mentioning
confidence: 99%